Sodobni inženirski materiali - Anžel, Ivan; Zupanič, Franc; Brunčko, Mihael (2025)
Advanced Engineering Materials. The script, Advanced Engineering Materials serves as a fundamental literature, primarily intended for students in master's study programs in Mechanical Engineering, Industrial Engineering, Mechatronics, and Product Design. The script is composed of three chapters: (i) Structure and Selection of Engineering Materials; (ii) Properties of Engineering Materials; (iii) Examples of Modern Engineering Materials. In the first chapter, the structure of metallic, ceramic, polymeric and composite materials is discussed, and criteria are presented that enable engineers to select appropriate materials for a specific application based on the desired combination of material properties. The second chapter addresses the properties of modern engineering materials with an emphasis on an in-depth study of the correlations between structure, microstructure, and properties. In the final and most extensive chapter, selected examples of modern engineering materials, whose application is currently very relevant in industrial practice, are presented. To name just the most interesting: dispersion-strengthened materials, shape memory alloys, engineering ceramics, hydrogen storage materials, rapidly solidified metallic materials, modern aluminium alloys, biopolymers, and many others.
Keywords: advanced engineering materials; structure; microstructure; properties; material selection